2021
DOI: 10.52547/iem.7.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Imipenem-Resistant Acinetobacter baumannii isolates in Iran: A Meta-Analysis

Abstract: Background: Acinetobacter baumannii is a gram-negative pathogen that is highly resistant to antibiotics. This bacterium can cause severe systemic infections, especially in hospitalized patients. Recently, antimicrobial-resistant Acinetobacter baumannii has become a lifethreatening pathogen in Iran and around the world. Materials & Methods: In this study, several Iranian and English databases were systematically searched to find all original and review articles investigating the prevalence of imipenem resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In recent years, the emergence of drug-resistant bacteria has been a public health concern in developing regions 28 30 . Excessive prescription of available antibiotics led to a mutation in bacteria and was conducive to the expansion of multidrug resistance in the bacteria, especially V. cholerae strains.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the emergence of drug-resistant bacteria has been a public health concern in developing regions 28 30 . Excessive prescription of available antibiotics led to a mutation in bacteria and was conducive to the expansion of multidrug resistance in the bacteria, especially V. cholerae strains.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria can lead to urinary tract infections, infectious poisoning, inflammation of the stomach or intestines, jaundice and infections of the abdominal cavity, pneumonia or wound infections ( 12 , 13 ). In the last decade, over-prescription or incorrect prescription of antibiotics has led to the emergence of antibiotic resistance to a significant extent ( 14 , 15 ). Microbial antibiotic resistance is a growing public health problem that complicates and increases the cost of medical treatment to $ 30 billion per year ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the frequency of resistance to antibiotics such as penicillins, cephalosporins, and carbapenems is increasing in beta-lactamase-producing species causing nosocomial UTIs, and causative microorganisms of CAUTI are more resistant than those of UTI due to the CAUTI being multi-bacterial [8,[13][14][15][16]. These highlight the important role of microbiological data in clinical judgement as well as the need for more regional and local studies on the characteristics of causative pathogens [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies and retrospective reviews conducted worldwide, including in Iran at both national and regional levels, indicated different epidemiological and antibiotic susceptibility patterns and related risk factors in patients with CAUTI [10,13,[18][19][20][21]. In some studies conducted in Iran, Escherichia coli has been reported as the most isolated pathogen from CAUTIs, but the frequency and the resistance pattern differ [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation